2021
DOI: 10.3390/ijms22094380
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen Activators in Neurovascular and Neurodegenerative Disorders

Abstract: The neurovascular unit (NVU) is a dynamic structure assembled by endothelial cells surrounded by a basement membrane, pericytes, astrocytes, microglia and neurons. A carefully coordinated interplay between these cellular and non-cellular components is required to maintain normal neuronal function, and in line with these observations, a growing body of evidence has linked NVU dysfunction to neurodegeneration. Plasminogen activators catalyze the conversion of the zymogen plasminogen into the two-chain protease p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 184 publications
0
8
0
Order By: Relevance
“…In run, these ECs produce pro-MMPs (MMP-2, MMP-3, and MMP-9) (Wang et al, 2003 ; Cheng et al, 2006 ; Suzuki et al, 2009 ). Subsequently, tPA converts the surface-bound inactive plasminogen (Plg) into active plasmin (Plm) (Doeuvre et al, 2010 ; Yepes et al, 2021 ). Plasmin, in turn, activates the MMPs, leading to the degradation of TJs and basal lamina (Mazzieri et al, 1997 ; Ramos-DeSimone et al, 1999 ; Monea et al, 2002 ; Rosenberg and Yang, 2007 ; Yang Y. et al, 2011 ).…”
Section: Bbb Breakdown In Normal Agingmentioning
confidence: 99%
“…In run, these ECs produce pro-MMPs (MMP-2, MMP-3, and MMP-9) (Wang et al, 2003 ; Cheng et al, 2006 ; Suzuki et al, 2009 ). Subsequently, tPA converts the surface-bound inactive plasminogen (Plg) into active plasmin (Plm) (Doeuvre et al, 2010 ; Yepes et al, 2021 ). Plasmin, in turn, activates the MMPs, leading to the degradation of TJs and basal lamina (Mazzieri et al, 1997 ; Ramos-DeSimone et al, 1999 ; Monea et al, 2002 ; Rosenberg and Yang, 2007 ; Yang Y. et al, 2011 ).…”
Section: Bbb Breakdown In Normal Agingmentioning
confidence: 99%
“…Urokinase (uPA) binding to uPAR activates the uPA/uPAR complex at the leading edge of migrating cell promoting their migration via extracellular matrix remodeling. These changes contribute to various physiological processes—morphogenesis, tissue regeneration and nerve fiber growth ( Parfenova et al, 2009 ; Tkachuk et al, 2009 ; Semina et al, 2016 ; Klimovich et al, 2020 ; Yepes et al, 2021 ), as well as to pathophysiological processes—fibrosis, tumor growth and metastasis ( Mahmood et al, 2018 ; Tkachuk et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…This therapy is usually administered within 4.5 h of stroke onset (Gravanis and Tsirka, 2008;Campbell et al, 2019) but can be extended to at least 9 h when imaging has confirmed the presence of salvageable tissue (Ma et al, 2019). Although tPA can promote cerebral reperfusion it also increases the risk of intracerebral hemorrhage (Gravanis and Tsirka, 2008;Vivien, 2017;Boese et al, 2020) and may negatively affect neuronal viability (Wang et al, 1998) and exert direct neurotoxic effects (Vivien, 2017;Zhu et al, 2019;Yepes et al, 2021). Overall, thrombolytic therapy benefits only ~20-25% of stroke patients (Vanacker et al, 2016;Stroke Foundation, 2017).…”
Section: Discussionmentioning
confidence: 99%